PERAN RELIGIO TRANSFORMATIONAL LEADERSHIP DAN KOMITMEN ORGANISASI DAN BAGAIMANA MENINGKATKAN KINERJA KARYAWAN MELALUI MEDIASI SHARIA ENGAGEMENT - Yudi Nur Supriadi; Dudi Imanuddin; Zenal Mutaqin (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2021)
This study aims to analyze the role of religious transformational leadership and organizational commitment in improving employee performance with the involvement of sharia as a mediation. This research was conducted on Islamic bank employees in DKI Jakarta, West Java, and Banten Indonesia Provinces. The number of research samples taken was 213 respondents. Hypothesis testing was carried out using SEM. The research findings show that religion transformational leadership has a positive effect on sharia engagement and employee performance, then organizational commitment has a positive effect on sharia engagement and employee performance, then sharia engagement has a positive effect on performance. The originality value of this research finds a new concept of religious transformational leadership and a research model that can support employee performance improvement in Islamic banking.